Minat Berwirausaha pada Teaching Factory Siswa Kuliner SMK Negeri 9 Padang - Nindya Syafitri; Ezi Anggraini; Elida Elida; Cici Andriani (Pusat Riset dan Inovasi Nasional, 2025)
Teaching Factory is a learning approach focused on real production and service activities, where students are directly involved in actual work processes. The main goal of this approach is to cultivate an entrepreneurial mindset among students. This study aims to explore the relationship between students’ interest in business and the implementation of the Teaching Factory (TeFa) program in vocational schools. The research was conducted on 11th-grade Culinary students at SMK Negeri 9 Padang. A quantitative method with a correlational approach was used. A total of 70 students participated as respondents, selected through proportional random sampling. Data was collected using a direct questionnaire based on a Likert scale, which had been tested for both reliability and validity. The results show a positive and significant relationship between students’ entrepreneurial interest and the implementation of the Teaching Factory among the 11th-grade Culinary students. Students’ entrepreneurial interest at SMK Negeri 9 Padang falls into the moderate category at 37%, and the implementation of the Teaching Factory is also in the moderate category at 33%.